Pelatihan Penggunaan Software Geogebra bagi Guru-Guru Matematika di Kabupaten Maros - Rosidah, Rosidah; Mulbar, Usman; Sahid, Sahid; T., Mar Athul Wazithah; Sa'diyyah, Fadhilah Nur (Jurnal Hasil-Hasil Pengabdian dan Pemberdayaan Masyarakat, 2025)
This Community Service Program (PKM) aims to improve the competence of mathematics teachers in Maros Regency through training on the utilization of GeoGebra software as an interactive learning medium. The background of this activity is the low mathematical understanding of students, partly due to teachers’ limited ability to use technology-based media. GeoGebra was chosen because it can facilitate the visualization of abstract mathematical concepts such as geometry, algebra, and calculus, making them easier for students to comprehend. The training was conducted at SMPN 1 Maros on July 23, 2025, involving junior high school mathematics teachers as participants. The implementation consisted of preparation, socialization, mentoring and supervision, as well as evaluation. The evaluation results showed that 90.75% of participants rated the program as highly relevant to their needs, 9.25% rated it relevant, and none rated it irrelevant. These findings indicate that the training successfully enhanced teachers’ skills in using GeoGebra and encouraged them to be more innovative in developing technology-based learning. Thus, this PKM activity has a positive impact on improving the quality of mathematics learning in Maros Regency.